1996
DOI: 10.1159/000291942
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Total Uterine Activity to Blood Loss in the Third Stage of Labour

Abstract: In 27 women, uterine activity in the third stage of labour was correlated with blood loss measured quantitatively during the same period of time. Myometrial activity was reflected by total intrauterine pressures measured using a Gaeltec® catheter tipped pressure transducer inserted transcervically within 5 min of delivery of the placenta. Blood loss over the same 2-hour period was collected on absorbent paper and measured in the laboratory by colorimetric measurement of the haemoglobin content. As total uterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 9 publications
(14 reference statements)
2
12
1
Order By: Relevance
“…In a previous study [5], we did not find any significant correlation between blood loss and total uterine activity in the third stage of labour, although a trend to a decrease in blood loss with an increase in intrauterine activity was observed. This was attributed to the biological variation of myometrial activity in different women.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In a previous study [5], we did not find any significant correlation between blood loss and total uterine activity in the third stage of labour, although a trend to a decrease in blood loss with an increase in intrauterine activity was observed. This was attributed to the biological variation of myometrial activity in different women.…”
Section: Discussioncontrasting
confidence: 67%
“…Laboratory methods of blood loss measurement are accurate but time consuming and tedious; moreover results of measurements cannot be obtained until hours after the event [4]. A previous study [5] did not show any significant correlation between total uterine activity immediately after delivery and blood loss during the same period of time. This was probably because of the wide biological variation in uterine activity in different women.…”
Section: Introductionmentioning
confidence: 92%
“…In efforts to understand the physiology of third stage, several studies monitored intrauterine pressures by inserting a catheter‐tipped pressure transducer transcervically within 5 minutes of delivery of the placenta. In 1996, Chua et al (6) conducted a study designed to compare uterine activity measured by catheter to blood loss as measured in a laboratory using absorbent paper and colorimetric measurement of hemoglobin content; in 1998, they showed reliability of the technique as a research methodology (7). The researchers found that increased activity in the third stage tended to be associated with an overall decrease in blood loss; however, the correlation was not a clear linear association.…”
Section: Blood Loss During Third Stagementioning
confidence: 99%
“…Other studies have used IUPCs following the expulsion of the placenta 7–10 . No cases were described in these studies that did not record contractions.…”
Section: Commentmentioning
confidence: 99%
“…No cases were described in these studies that did not record contractions. The description of the insertion was the same as in this study 7–10 . The uterine activity was reported in a summative manner rather than providing contraction frequency and intensity, because sometimes uterine contractions following placental expulsion would be tetanic or hypertonic, such that return of the contraction curve to the baseline took several minutes 10 .…”
Section: Commentmentioning
confidence: 99%